2018
DOI: 10.1108/apjml-04-2017-0073
|View full text |Cite
|
Sign up to set email alerts
|

How website quality affects online impulse buying

Abstract: Purpose The purpose of this paper is to investigate the impact of website quality on online impulse buying behavior (OIBB) in China, and assess the moderating roles of sales promotion and credit card use. Design/methodology/approach An online and personal survey from 1,161 online shoppers belonging to three big cities of China – Beijing, Shanghai, and Nanjing – was conducted. A random sampling technique was utilized for data collection. Data were analyzed using validity and reliability tests, confirmatory fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
157
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(194 citation statements)
references
References 71 publications
20
157
0
17
Order By: Relevance
“…In line with Akram et al (2018) and Badgaiyan and Verma (2015), sales promotion affected impulse buying as a moderating variable. From Table 4, the regression coefficient of interaction between website quality and sales promotion (standardized β = 0.141, t =2.818, p<0.01) was found significant with a positive slope.…”
Section: Reliability and Validity Analysissupporting
confidence: 55%
See 1 more Smart Citation
“…In line with Akram et al (2018) and Badgaiyan and Verma (2015), sales promotion affected impulse buying as a moderating variable. From Table 4, the regression coefficient of interaction between website quality and sales promotion (standardized β = 0.141, t =2.818, p<0.01) was found significant with a positive slope.…”
Section: Reliability and Validity Analysissupporting
confidence: 55%
“…Types of sales promotion employed in e-commerce sites/platforms can be distinguished based on the types of customers (new and returning customers). Akram et al (2018) suggested using monetary sales promotion to lure new customers, while returning customers may be enticed with non-monetary sales promotion (gifts, bonus, or contests and sweepstakes).…”
Section: Reliability and Validity Analysismentioning
confidence: 99%
“…The high level of security of a website will affect consumer buying behavior (Wells, Parboteeah, & Valacich, 2011). A website is considered safe if the user feels safe when making transactions, administrators do not misuse consumers' personal data, and the security and privacy policies are clearly displayed (Akram et al, 2018).…”
Section: Web Quality and Online Behavior Intentionmentioning
confidence: 99%
“…Navigabilty is very closely related to the ease of using websites. Some researchers such as (Akram et al, 2018;Turkyilmaz, Erdem, & Uslu, 2015;Wells et al, 2011) state that navigabilty or ease to use has a positive and significant effect on consumer buying behavior. Navigabilty has a positive relationship with intention to use (Semuel, Wijaya, & Devie, 2019).…”
Section: Web Quality and Online Behavior Intentionmentioning
confidence: 99%
See 1 more Smart Citation